An electrochemical technique for controlled dissolution of zirconium based components of light water reactors. Issue 4 (14th January 2019) - Chatterjee, Sayandev; Fujimoto, Meghan S.; Canfield, Nathan L.; Elmore, Monte R.; Olson, Devin W.; Buck, Edgar C.; Conroy, Michele A.; Varga, Tamas; Senor, David J.
Abstract : This work demonstrates a controlled potential electrochemistry with correlative microscopy for insight into the radial H-distribution into TPBAR components of light water reactors. Abstract : Zircaloy-4 (Zr-4) based liners and getters are the principle functional components of Tritium-Producing Burnable Absorber Rods (TPBARs) in light water nuclear reactors where they reduce tritiated water into tritium gas. Upon tritium exposure, zirconium tritide is formed, which changes the chemical composition, structure and morphology of these materials. Their thermodynamic properties are affected by (i) the hydride phase identity, (ii) radial and spatial tritide/hydride (T/H) distribution, and (iii) the changes in structure and morphology of the material upon T/H-migration, and their comprehensive knowledge is needed to predict performance of these materials. This work demonstrates that controlled potential electrochemistry techniques to be highly efficient for controlled oxidative radial dissolution of Zr-4 based liners (both unloaded and loaded with hydride/deuteride as chemical surrogates for tritium). The electrodissolution is further combined with microscopic techniques to accurately determine the distribution of hydride phases. This work demonstrates a reliable technique for radially etching the liners after irradiation to provide insight into the radial and spatial distribution of tritium within the TPBAR, improving the fundamental understanding of tritium transport and providing a basis for validating predictive models.